Meta-analysis of right ventricular function in patients with aortic stenosis after transfemoral aortic valve replacement or surgical aortic valve replacement - Yunshan Cao; Vikas Singh; Aqian Wang; Liyan Zhang; Tingting He; Hongling Su; Rong Wei; Yichao Duan; Kaiyu Jiang; Wenyu Wu; Yan Huang; Sammy Elmariah; et al. (SAGE Publishing, 2020)
Background: Right ventricular function (RVF) is an independent predictor of prognosis for patients undergoing aortic valve replacement: transcatheter aortic valve replacement (TAVR) or surgical aortic valve replacement (SAVR). The effect of transfemoral aortic valve replacement (TF-TAVR) on RVF is uncertain. We aimed to perform a meta-analysis of the effect of TF-TAVR on RVF in patients with aortic stenosis (AS) and compare the effect of TF-TAVR with SAVR. Methods: We searched relevant studies from PubMed, Embase, Cochrane Library databases, and Web of Science. Furthermore, two reviewers (Wang AQ and Cao YS) extracted all relevant data, which were then double checked by another two reviewers (Zhang M and Qi GM). We used the forest plot to present results. Tricuspid annular plane systolic excursion (TAPSE) was the primary outcome. Results: This meta-analysis included 11 studies. There were 353 patients who underwent TF-TAVR, and 358 patients who were subjected to SAVR. There was no significant difference in TAPSE at 1 week and 6 months as well as right ventricular ejection fraction (RVEF) at <2 weeks and 6 months after TF-TAVR. For the SAVR group, TAPSE at 1 week and 3 months as well as fractional area change (FAC) at 3 months post procedure were significantly aggravated, while RVEF did not change significantly. Moreover, TAPSE post-TF-TAVR was significantly improved as compared with post-SAVR. The △TAPSE, the difference between TAPSE post-procedure and TAPSE prior to procedure, was also significantly better in the TF-TAVR group than in the SAVR group. Conclusion: RVF was maintained post TF-TAVR. For SAVR, discrepancy in the measured parameters exists, as reduced TAPSE indicates compromised longitudinal RVF, while insignificant changes in RVEF implicate maintained RVF post procedure. Collectively, our study suggests that the baseline RV dysfunction and the effect of TF-TAVR versus SAVR on longitudinal RVF may influence the selection of aortic valve intervention.